The Role of SARS1 in Head and Neck Squamous Cell Carcinoma and its Potential as a Diagnostic and Prognostic Biomarker - Qifeng Zhang; Mengting Liu; Jiong Lv; Youjian Peng; Dongjie Fu; Yan He (International Dental Journal, 2025)
Objective: Recurrent or locally advanced head and neck squamous cell carcinoma (HNSCC) carry a poor prognosis due to its aggressive invasiveness and resistance to conventional chemotherapy. Identifying effective biomarkers for early detection and prognostic assessment is crucial to enhance treatment efficacy and reduce mortality rates in HNSCC patients. This study aimed to investigate the role of seryl-tRNA synthetase (SARS1), a crucial enzyme in protein synthesis, as a potential biomarker and therapeutic target for HNSCC. Materials and methods: In the analysis of SARS1 expression and its functional correlation in HNSCC, comprehensive bioinformatics analyses were integrated with pathological sample evaluation, alongside methods such as real-time PCR, Western blotting, immunohistochemistry, cell viability assays, wound-healing tests, and flow cytometry. Results: SARS1 was significantly overexpressed in HNSCC tissues compared with normal tissues at both mRNA and protein levels (P < .05). High SARS1 expression was associated with poor overall survival (1.58 [1.18-2.11], P < .05, OS), disease-specific survival (1.94 [1.28-2.43], P < .05, DSS), and progression-free survival (1.76 [1.38-2.25], P < .05, PFS). Knockdown of SARS1 in HNSCC cell lines inhibited cell viability, migration, and colony formation while promoting apoptosis. Mechanistically, SARS1 activated the PI3K-AKT signalling pathway, which is a key regulator in tumour progression. SARS1 expression was not significantly associated with immune cell infiltration in HNSCC. Conclusion: The findings suggest that SARS1 is a novel oncogenic driver in HNSCC and could serve as a potential biomarker for poor prognosis. Its ability to promote HNSCC progression through activation of the PI3K-AKT pathway highlights its potential as a therapeutic target. Further research is needed to explore its role in tumour immune evasion and validate its utility in clinical applications.